2019
DOI: 10.1590/1980-549720190047
|View full text |Cite
|
Sign up to set email alerts
|

Hanseníase em menores de 15 anos no estado do Tocantins, Brasil, 2001-2012: padrão epidemiológico e tendência temporal

Abstract: RESUMO: Introdução: O Tocantins é o estado mais hiperendêmico para hanseníase no Brasil. Objetivo: Descrever as características epidemiológicas e tendências temporais dos indicadores da hanseníase em menores de 15 anos de idade no Tocantins entre 2001-2012. Metodologia: Análise de dados do Sistema de Informação de Agravos de Notificação (SINAN). Incluíram-se casos novos de menores de 15 anos residentes no estado. Calcularam-se os indicadores e analisaram-se as tendências temporais por meio da regressão… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
2
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 25 publications
(40 reference statements)
1
7
2
5
Order By: Relevance
“…The Southeast, South and North regions showed a decreasing trend, while the Northeast and Central-West regions showed a stable trend. These results are consistent with other studies of leprosy conducted in Brazil, which have generally shown a reduction in the burden of leprosy in Brazil [45][46][47].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The Southeast, South and North regions showed a decreasing trend, while the Northeast and Central-West regions showed a stable trend. These results are consistent with other studies of leprosy conducted in Brazil, which have generally shown a reduction in the burden of leprosy in Brazil [45][46][47].…”
Section: Discussionsupporting
confidence: 92%
“…The presence of leprosy disabilities is an indicator of late diagnosis and treatment [41][42][43]. This underscores the need to de ne and strengthen public health interventions aimed at early diagnosis and comprehensive care of people affected by M. leprae, especially those with severe forms of the disease, in order to reduce disability, mitigate associated stigma, and reduce disease transmission [42,[44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…The challenge is to overcome all obstacles related to factors that influence the diagnosis of children and adolescents, such as stigma and prejudice, socioeconomic conditions, and difficulties in carrying out the examination in children. To reduce the disease in childhood, early diagnosis and the thorough examination of contacts are essential, as intimate intra-household contacts are the main transmitters [ 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Segundo os autores, a forma dimorfa ratifica a manutenção da cadeia de transmissão da hanseníase e a necessidade da prevenção e ampliação de ações de controle da doença. Tal predominância não foi observada por Monteiro et al (2019) no estado de Tocantins, onde prevaleceu a forma clínica indeterminadaapresentações iniciais da doença quando considerados período de exposição e incubação.…”
Section: Discussionunclassified